2007
DOI: 10.1093/nar/gkm964
|View full text |Cite
|
Sign up to set email alerts
|

DBD––taxonomically broad transcription factor predictions: new content and functionality

Abstract: DNA-binding domain (DBD) is a database of predicted sequence-specific DNA-binding transcription factors (TFs) for all publicly available proteomes. The proteomes have increased from 150 in the initial version of DBD to over 700 in the current version. All predicted TFs must contain a significant match to a hidden Markov model representing a sequence-specific DNA-binding domain family. Access to TF predictions is provided through http://transcriptionfactor.org, where new search options are now provided such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
232
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(244 citation statements)
references
References 24 publications
7
232
0
3
Order By: Relevance
“…Mammalian genomes encode at least 2000 DNA binding proteins (Wilson et al 2008), and we anticipate that ChIP-seq experiments using antibodies for other TFs would identify binding sites in different subsets of the distal H3K4me1-marked regions than we found associated with STAT1 and FOXA2 in the current work. Consistent with this, we demonstrated that a majority of the large number of distal regions that were symmetrically flanked by H3K4me1 had sequence properties that were expected for regulatory regions.…”
Section: Discussionmentioning
confidence: 72%
“…Mammalian genomes encode at least 2000 DNA binding proteins (Wilson et al 2008), and we anticipate that ChIP-seq experiments using antibodies for other TFs would identify binding sites in different subsets of the distal H3K4me1-marked regions than we found associated with STAT1 and FOXA2 in the current work. Consistent with this, we demonstrated that a majority of the large number of distal regions that were symmetrically flanked by H3K4me1 had sequence properties that were expected for regulatory regions.…”
Section: Discussionmentioning
confidence: 72%
“…TFs were selected from two database resources (Transcriptionfactor.org, PfamTOGo website) as well as previous studies on this topic (6,16,55). In all cases, we defined a univocal one-to-one relationship between TF class and DBD class.…”
Section: Methodsmentioning
confidence: 99%
“…The mapping is based on annotation files provided by Ensembl, NCBI and Affymetrix. Additional functional annotations are obtained from MGI (Bult et al, 2008), ZFIN (Sprague et al, 2006), DBD (Wilson et al, 2008) and KEGG (Kanehisa et al, 2010) by mapping their respective data to the corresponding Ensembl and Entrez gene models in Manteia.…”
Section: Manteiamentioning
confidence: 99%
“…The mapping is based on annotation files provided by Ensembl, NCBI and Affymetrix. Additional functional annotations are obtained from MGI (Bult et al, 2008), ZFIN (Sprague et al, 2006), DBD (Wilson et al, 2008) and KEGG (Kanehisa et al, 2010) by mapping their respective data to the corresponding Ensembl and Entrez gene models in Manteia.The conservation analysis among mouse, chicken and zebrafish was based on ortholog predictions performed with InParanoid (Berglund et al, 2008) and Ensembl Compara. This prediction was used in Manteia to identify and re-annotate poorly annotated gene models using their ortholog data.…”
mentioning
confidence: 99%